Revisiting the World’s Strictest COVID-19 Lockdown: Formidable Mental Health Challenges - Guan, Beier; Li, Ruihua; Huang, Chuanning; Du, Jiang; Zhao, Min; Liu, Shuyan (Pharmacopsychiatry, 2023)
Introduction Many nations have implemented lockdowns to prevent and minimize the spread of infections in healthcare settings. However, the impact of lockdown duration on mental health remains controversial.Methods We conducted a retrospective study using online questionnaires to assess the mental health status of the general population during the Shanghai lockdown period from March to May 2022. The mental health of the participants was evaluated by the 12-item General Health Questionnaire (GHQ-12), in which a cut-off score of 12 or more indicated psychological distress. A logistic regression model was used to evaluate the relationship between lockdown duration and mental health.Results Among 2139 participants (mean age: 26.12 years, standard deviation: 6.37, 731 females; 1378 unmarried; 1099 Shanghai residents), approximately 47% reported psychological distress (GHQ-12≥12). Participants exposed to lockdown reported significantly higher GHQ-12 scores (11.93±6.81 vs. 8.73±6.35, p<0.001). In our logistic regression model, participants who experienced the longest lockdown (43–61 days) had a significantly higher risk of psychological distress compared with those who did not (odds ratio: 3.10, 95% confidence interval: 2.06–4.70, p<0.001).Discussion Lockdown duration significantly affects mental health, with longer lockdown duration being associated with worse mental health status. The relationship between lockdown and mental health should not be neglected in case of lockdown in response to future pandemics.
Keywords: COVID-19; pandemic; public mental health; psychological impact